Review of the Feasibility and Implications of the Framework for Subsea Power Generation in the Niger Delta (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study develops and evaluates a framework for subsea power generation tailored to the Niger Delta, addressing persistent deficiencies in conventional onshore electricity systems. Using a multidisciplinary approach, the research integrates technical feasibility, economic analysis, environmental impact assessment, and comparative performance evaluation. Key parameters, including tidal velocity, seabed conditions, and system reliability, were analyzed alongside life cycle and cost metrics. Findings indicate that subsea systems offer improved energy efficiency, enhanced reliability, and reduced environmental footprint compared to conventional onshore methods. Economic modeling suggests long-term cost competitiveness despite high initial capital expenditure. The study further demonstrates that localized environmental and geotechnical considerations are critical to system optimization. Overall, the proposed framework presents a viable pathway for sustainable energy development, with significant implications for energy security, industrial growth, and environmental stewardship in the Niger Delta.